Serum glycated albumin is associated with in-stent restenosis in patients with acute coronary syndrome after percutaneous coronary intervention with drug-eluting stents: An observational study - Lin, Xiao Long; Li, Qiu Yu; Zhao, Dong Hui; Liu, Jing Hua; Fan, Qian (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous studies have been confirmed the predicted value of Serum glycated albumin (GA) in atherosclerotic cardiovascular disease. However, The relationship between GA and the development of in-stent restenosis (ISR) after drug-eluting stent (DES) implantation has not been verified in patients with the acute coronary syndrome (ACS). Method: 797 patients diagnosed with ACS who underwent re-coronary angiography more than six months after the first successful DES-based percutaneous coronary intervention (PCI) were eventually included in this study. Patients were categorized into two groups based on the median GA levels of 14.94%. Moreover, multivariate logistic regression analysis models, the net reclassification improvement and integrated differentiation improvement risk models were constructed to assess the relationship between the GA and DES-ISR with ACS patients. Results: The GA was significantly association with an increased risk of DES-ISR, Upon adjusting for confounding factors (As nominal variate: OR 1.868, 95% CI 1.191–2.932, P = 0.007; As continuous variate: OR 1.109, 95% CI 1.040–1.183, P =0.002). The addition of GA to a baseline risk model and an incremental effect on the predictive value for DES-ISR (AUC: GA vs. Baseline model, 0.714 vs. 0.692, comparison P = 0.017; Category-free net reclassification improvement (NRI) 0.080, P = 0.035; integrated discrimination improvement (IDI) 0.023, P < 0.001). Conclusion: GA level was significantly associated with a high risk of DES-ISR in patients with ACS treated with PCI. Moreover, the addition of the GA to a baseline risk model has an incremental effect on the predictive potential for DES-ISR.